How Destination Image, Service Quality, and Customer Experience Drive Visit Intention Through Perceived Value at Tlocor - Putri Trivia, Dyva; Halik, Abdul; Yanu Alif Fianto, Achmad (Journal of Applied Management and Business, 2025)
Maritime tourism destinations face increasing challenges in understanding factors that drive visitor behavioral intentions, particularly in conservation oriented contexts. This study aims to examine how destination image, service quality, and customer experience influence visit intention through perceived value as a mediating mechanism at Tlocor Marine Tourism, Pulau Lusi, Sidoarjo, East Java, Indonesia. The research employs a quantitative correlational approach using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected through offline surveys administered to 100 respondents comprising actual and potential visitors. The study utilized a structured questionnaire with a 5 point Likert scale to measure all constructs, and relationships were tested using SmartPLS 4 software. The research results demonstrate that service quality exhibited the strongest direct effect on perceived value (β = 0.566, p < 0.001), followed by customer experience and destination image. More importantly, perceived value significantly mediated the relationships between all three antecedent variables and visit intention, with Variance Accounted For (VAF) ranging from 40.0% to 52.6%, indicating partial mediation effects. The structural model achieved high explanatory power, explaining 82.3% of variance in perceived value and 79.1% in visit intention. These findings suggest that perceived value emerges as a critical psychological mechanism translating destination characteristics and service experiences into behavioral intentions. The study provides empirically grounded recommendations for destination management organizations to develop value focused marketing strategies and implement integrated service quality improvements for sustainable maritime tourism development.